Modelling and fault-tolerant control of 5-phase induction machine - Rolak, M.; Che, H.S.; Malinowski, M. (De Gruyter Open, 2015)
The paper presents modeling and analysis of a 5-phase induction machine connected to 2-level 5-leg converter in case of open-phase failure. A control of the machine is accomplished using the Field Oriented Control with hysteresis current controllers. Moreover, a fault-tolerant algorithm is addressed and simulated.